The Evaluation of Doppler Indices for Umbilical Artery in Hypertensive Women in Third Trimester of pregnancy - Rasool , Zarish; Batool , Narjis; Ali, Abid; Arshad, Nosheen; Mahmood Dar , Waqar (Medical Science Journal for Advance Research, 2022)
Background: The hypertensive disorders affect pregnant women and can create complications for the women in last trimester of pregnancy. To assess the impact of high hypertension, doppler scan is recommended in the third trimester. Objective: Present explores values of PSV, EDV, S/D ratio, RI and PI among normotensive and hypertensive pregnant women during third trimester of pregnancy in Islamabad, Pakistan. Material and Methods: A Cross-sectional study was conducted at PIMS hospital Islamabad with objectives to evaluate doppler indices in fetal umbilical artery among hypertensive pregnant women in the third trimester of pregnancy. Data were collected from 1st February 2022 to 15th May 2022. A total of 93 pregnant women were recruited from already registered at maternal child health care center of PIMS and recommended for doppler indices scan. Toshiba Aplio 300 Ultrasound System was used for the assessment. Data about S/D ratio, RI and PI was analyzed by using IBM SPSS® software platform. Results: Mean Age of pregnant women in our study conducted was 26.722 ± 4.133. Also the mean gestational week for pregnant women was 32.163 ± 2.35. Doppler indices were significantly raised in hypertensive women as compared to normotensive women. Doppler indices i.e. Pulsatility Index (Mean 1.049 ± 0.312 vs 1.360 ± 0.421), Resistivity Index (Mean 0.631 ± 0.114 vs 0.743 ± 0.01), Systolic/Diastolic flow (Mean 2.672 ± 0.512 vs 3.818 ± 0.986) were increased in third trimester of hypertensive women as compared to normotensive patients. Conclusion: In this study, among doppler indices pulsatility index and resistivity index were identified as significant after applying null hypothesis test. Doppler ultrasound should be used to identify vascular resistance and evaluating degree of fetoplacental blood flow in hypertensive pregnant women.